2010
DOI: 10.1080/02602930802563094
|View full text |Cite
|
Sign up to set email alerts
|

Web‐based student feedback: comparing teaching‐award and research‐award recipients

Abstract: We examined web-based ratings and open-ended comments of teaching-award winners (n = 120) and research-award winners (n = 119) to determine if teachingaward winners received more favourable ratings and comments on RateMyProfessors.com. As predicted, students rated teaching-award winners higher than research-award winners on measures of teaching quality (i.e. helpfulness and clarity). A higher percentage of teaching-award recipients relative to research-award recipients received positive open-ended comments abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…However, the validity of those evaluations according to Jones, Gaffney-Rhys and Jones (2012) and Clayson (2013) is relatively low and prone to cognitive biases, so the general suggestion is not to use this data as a base for remuneration systems. Research has found that a first impression had a great effect on the score of student evaluation, additionally the use of humour, clarity, appearance and personality of lecturers is of great importance in regards to the results of students' evaluations, thus the quality of these evaluations is highly questionable and they should be handled with care (Symbaluk and Howell 2010). These results are controversial; objects or research are different and varied.…”
Section: Browne and Rayner 2015 (England Higher Education)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the validity of those evaluations according to Jones, Gaffney-Rhys and Jones (2012) and Clayson (2013) is relatively low and prone to cognitive biases, so the general suggestion is not to use this data as a base for remuneration systems. Research has found that a first impression had a great effect on the score of student evaluation, additionally the use of humour, clarity, appearance and personality of lecturers is of great importance in regards to the results of students' evaluations, thus the quality of these evaluations is highly questionable and they should be handled with care (Symbaluk and Howell 2010). These results are controversial; objects or research are different and varied.…”
Section: Browne and Rayner 2015 (England Higher Education)mentioning
confidence: 99%
“…These should be seen as one possibility, the results are merely an indication and provide necessary input for development; however, no sweeping conclusions should be drawn on their basis. In spite of significant positive developments with regards to student surveys, various studies also point to the unreliability of student ratings (Jones et al 2014, Clayson 2013, where first impressions and likeability of the teacher's personality play an important part (Symbaluk and Howell 2010).…”
Section: The Particularities and Effectiveness Of The Pm Systems Of Umentioning
confidence: 99%
“…Two other studies examined the validity of RMP ratings using different approaches. Symbaluk and Howell (2010) compared the RMP ratings of teaching-award winners and those of research-award winners. The sample includes 120 winners of 3M Teaching Fellowship and 119 winners of Killam Research Fellowship in Canada.…”
Section: Related Literature On Rmpmentioning
confidence: 99%
“…Gannon (2018) also suggested that despite the potential biases in student evaluation, it is still the best available measure of teaching effectiveness. Symbaluk and Howell (2010) concluded that even with the potential biases in student evaluations, they are reasonably valid measures of teaching effectiveness. RMP is a website on which students can leave their ratings and comments of faculty members.…”
Section: Introductionmentioning
confidence: 99%
“…The primary goal of normal universities should be switched to preparing students for practice, which entails rectifying the current marginality of teacher education and according equitable value to teaching. Teaching-oriented staff should be accredited for their unfailing commitment to their teaching career, and their generally higher level of teaching quality than research-active staff (Symbaluk & Howell, 2010). Demands on teachers' research outcomes need to be re-examined to set realistic expectations, given the high level of investment required for research activities, the inverse relationship between quantity and quality of research, institutional characteristics and practical constraints.…”
Section: Establishing a Fair Faculty Assessment Systemmentioning
confidence: 99%